Factors influencing drop-out of households from community based health insurance membership in rural districts of Gurage Zone, Southern Ethiopia: Community based case-control study - Zepre, Kebebush; Yassin, Fedila; Tadesse, Betelhem; Tolossa, Omega; Hailemariam, Derbachew; Wondimu, Asegedech; GebreEyesus, Fisha Alebel; Tsehay, Tadesse; Assfa, Kenzudin (Frontiers in Public Health, 2022)
Background: Financial risk sharing through community based health insurance is a critical component for universal health coverage however; its development is in a great challenge not only due to low enrolment but also due to high drop-out rate of members from the scheme that clearly threaten its sustainability. So far, the existing few studies in this area focused on household’s enrolment to community based health insurance, rather than drop out. This study aimed to identify factors influencing households to drop-out from community based health insurance membership in rural districts of Gurage zone, southern, Ethiopia. Methods: A Case- control study was carried out at community level from May to July 2021. Supplemented by qualitative focus group discussions. Multi-stage random sampling was employed to select districts and kebeles, simple random sampling was applied to select each participant. Interviewer administered prearranged tool was used for collecting data. Epi-data version 3.1 and SPSS version 21 were used for data entry and analysis. Association between factor and outcome variable were done using binary logistic regression analysis at p <0.5 and 95% CI. Qualitative data were analyzed thematically and triangulated. Results: In our study highest wealth status (adjusted odds ratio [AOR] =2.36, 95% confidence interval [CI]:1.14-4.87), unfavorable attitude towards CBHI (AOR: 1.81, 95% CI: 1.87-3.37), no illness experience in the last 3 month (AOR: 5.21, 95% CI: 2.90-9.33). no experience in frequent health facility visit (AOR:5.03,95% CI:1.17-23.43),exposure to indigenous community insurance (AOR:0.10,95% CI: 0.03-0.37), not graduated in model house hold( AOR: 3.20, 95% CI:1.75-5.83), length of stay as member in the scheme for more than three years (AOR:0.55,95% CI: 0.29-0.94), not trusting governing bodies (AOR:10.52,95% CI:4.70-23.53), ordered drug not available in the contractual facility (AOR:14.62,95% CI:5.37-39.83), waiting time greater than 3 hours (AOR:4.26,95% CI:1.70-10.66) and poor perceived service quality (AOR:12.38,95%CI:2.46-62.24)were statistically significant influencing factors associated with dropout from community based health insurance.